Nutritional interventions on quality of life in cancer patients during treatment: a systematic review - Ouologuem, Abdoulaye (My University, 2025)
Cancer is a global health issue, with chemotherapy and radiotherapy as the primary treatment options. These treatments can induce side effects that impair patients’ quality of life. Various diets have been shown to positively affect symptoms such as nausea and vomiting, potentially providing an alternative to alleviate the negative impacts of cancer treatments. This systematic review aims to evaluate the impact of nutritional interventions on improving the adverse effects associated with cancer treatments. A search was conducted in PubMed using MeSH terms, resulting in the inclusion of 39 articles. The most common types of cancer represented were multiple cancers (n = 12), followed by breast cancer (n = 11). Twelve studies were dietary related, 14 were non-nutrient, and 13 were nutrient interventions. Personalized diet or dietary education was featured in (n = 7) studies, while ginger was examined in (n = 5). Most studies included in this review demonstrated that nutritional interventions benefit cancer treatment side effects, leading to enhanced quality of life of cancer patients. These findings can assist clinicians in advising patients with non-medical options to alleviate the adverse effects of cancer treatments. Further studies involving more patients are necessary to confirm these findings.
Keywords: Cancer treatment; Nutritional intervention; Diet; Patients; Quality of life; Side effects